Exploring linguistic and narrative competence in Italian children with developmental language disorder: A comparative study with typically developing peers. - Zanchi, Paola; Provera, Alessandra; Zampini, Laura (Clinical Linguistics & Phonetics, 2025)
Developmental Language Disorder (DLD) is a clinical condition characterised by language difficulties without cognitive or neurological impairments, leading to communication and learning challenges. The study explores the narrative and linguistic abilities of children with DLD and Typically Developing (TD) peers by analysing both macrostructural and microstructural aspects of their narrative production elicited during a storytelling task and describing the types of grammatical and lexical errors. Participants included 19 children with expressive DLD aged 4–8 years and 19 TD children matched by age and gender. Narrative competence was assessed using the Narrative Competence Task (NCT), a storytelling task which evaluates narratives at both the macrostructure and microstructure levels. The grammatical and lexical errors were coded using an ad hoc coding scheme based on the existing literature. The results showed no significant differences in macrostructural aspects of narratives between the two groups. However, at the microstructural level, children with DLD produced shorter utterances. Considering the type of errors produced in narratives, overall, children in the two groups made a small amount of errors (with an average of 2 errors in 100 words). The study contributes to deepening our understanding of the linguistic profile of Italian children with expressive DLD, emphasising the importance of tailored interventions and personalised training programs.